«Обліковець» масових убивств у добу «Великого терору» (Соломон Абрамович Альтзіцер) - Золотарьов, В.; Бажан, О. (Краєзнавство, 2017)
На основі архівних документів висвітлюється біографія та діяльність секретаря особливої трійки
при Київському управлінні НКВС в 1937-1938 роках Соломона Альтзіцера. On the basis of archival documents, the biography and activities of the secretary of the special troika under
the Kyiv NKVD administration in 1937-1938 , Solomon Altsitzer, are covered. An attempt is made to disclose the
principles of the registration and statistical departments of the Main Department of State Security of the NKVD of
the USSR during the Great Terror. The biography of the heads of the accounting and statistical department of the
State Security Department of the NKVD of the UkrSSR from the end of the 1920s-1930s is presented in the essay.
A significant place in the article is given to the clarification of the extrajudicial powers of the NKVD, especially
the functioning of extrajudicial sentencing bodies that existed in 1937-1938. It is concluded that the three NKVD
guided by the simplified procedure of legal proceedings, not adhering to most of the normative requirements of the
then Code of Criminal Procedure of the USSR, resulting in massive loss of innocent people. На основании архивных документов воссоздана биография и деяльность секретаря особой тройки
при Киевском управлении НКВД в 1937-1938 годах Соломона Альтзицера.